Analysis Of Consumer Purchase Decision Towards Collaborative Packaging Design Products Of Dear Me Beauty And KFC - Siti Masrika; Dini Faisal (Jurnal Kajian dan Penelitian Umum, 2023)
This research aims to determine the influence of packaging design variables from the collaboration between Dear Me Beauty and KFC on consumer purchasing decisions. Respondents for this study were selected using purposive sampling technique, where the respondents were consumers who purchased and used products resulting from the collaboration between Dear Me Beauty and KFC. A total of 84 respondents were included in the research sample. The data collection method employed in this study involved using a Likert-scale questionnaire. The variables studied in this research are collaborative packaging design (as variable X) and purchasing decisions (as variable Y). This study adopts a quantitative approach, and the questionnaire data are analyzed using descriptive statistics." The results of the study with 84 respondents indicate that the highest percentage for the collaborative packaging design variable (variable X) falls under the 'agree' classification, with a frequency score of 131 and a percentage of 31.19%. This suggests that respondents are attracted to the visual appeal and practicality of the design, leading them to decide to purchase products resulting from the cross-disciplinary collaboration between Dear Me Beauty and KFC. Additionally, for the purchasing decision variable (variable Y), the highest percentage also falls under the 'agree' classification, with a frequency score of 76 and a percentage of 30.16%. This demonstrates that respondents make purchases based on packaging factors and their need for the product."